Pengaruh Persepsi Harga Kualitas Produk dan Kualitas Pelayanan Terhadap Keputusan Pembelian di Mobicoffee Rest Area KM 166A - Dea ayu; Salman Paludi (Human Capital Development, 2022)
The purpose of this activity is to analyze the influence of perceptions of price, product quality, and service quality on purchasing decisions in the Mobicoffee Rest Area KM 166A. in this analysis the population of Mobicoffee visitors. The sampling method used was non-probability sampling, along with the accidental sampling method, a total of 100 respondents who visited Mobicoffee. The data collection method that uses a data processing questionnaire is measured by a choice of 5 Liker scales that have been tested for validity and reliability. This analysis uses classical assumption tests, and multiple linear regression analysis with SPSS 25.0 software. The results of the study showed that the perception of price, product quality, and service quality partially had a positive and significant effect on purchasing decisions and simultaneously the variables of price perception, product quality, service quality had a positive and significant influence on purchasing decisions in Mobicoffee Rest Area KM 166A